Bee forage mapping based on multispectral images Landsat 8 - Moskalenko, A. (Land Management, Cadastre and Land Monitoring, 2017)
Possibilities of bee forage identification and mapping based on multispectral imageshave been shown in the research. Spectral brightness of bee forage has beendetermined with the use of satellite images. The effectiveness of some methodsof image classification for mapping of bee forage is shown.Keywords: bee forage, mapping, multispectral images, image classification.